Keanekaragaman Jenis Tumbuhan Obat di Kawasan Cagar Alam Mutis Timau, Kabupaten Timor Tengah Selatan, Provinsi Nusa Tenggara Timur (Studi Kasus Jalur Akses Desa Penyangga (Desa Fatumnasi dan Desa Nenas) Kecamatan Fatumnasi, Kabupaten Timor Tengah Selatan - Sarida Oktavia Deku; Nixon Rammang; Norman P. L. B. Riwu Kaho; Lusia Sulo Marimpan (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2025)
East Nusa Tenggara Province has a diversity of medicinal plants and traditional cultures in utilizing them. The use of plants as traditional medicine has been inherited from generation to generation by the community around the Mutis Timor Nature Reserve Area, South Central Timor Regency. This study aims to find out the diversity of plant species, the efficacy ofthese plants and how to process plants as traditional medicine by the community around the Mutis Timau Nature Reserve Area. The data collection technique uses the Snowball Sampling interview method, observation, vegetation analysis with the roaming method to obtain plant locations and the Line Transek Plot method to analyze vegetation and literature studies. Data analysis uses quantitative analysis to determine the Important Value Index, Diversity, Wealth, Equity and Similarity of Types.The results of the study found as many as 33 types of plants with medicinal properties, with the composition of vegetation showing that the types of plants with more herbaceous habitus were 18 types, 7 types of shrubs, 4 types of trees, 2 types of shrubs and lianas. The types of medicinal plants that have the largest Important Index Value are Eucalyptus urophylla (216.84) for thetree and pole level, Croton caudatus (115.81) for the stake level, Centella asiatica. L (45.94) for seedling rate. The value of the Plant Diversity Index in the Mutis Timau Nature Reserve ranges from 1.128-2.745 (moderate), the value of the Wealth Index at the level of trees, poles, and piles has a value in the range of 1.098-1.808 (low) while at the seedling level has a value of 5.638 (high), the value of the evenness index at the tree and pole level ranges from 0.5149-0.5286 (fairly even), the stake level has a value of 0.8165 (almost evenly) while at the seedling level it has a value of 0.4206 (less evenly) andThe value of the similarity index ranges from 0.146-0.4783 (low).